The Influence of Blended Learning on Learning Loss Problems in Class Vii Social Sciences Learning at SMPN 1 Pameungpeuk - Iwan Setiawan, Iwan Setiawan; Tetep; Ade Suherman (SAHUR Journal, 2024)
This research is motivated by problems in social studies learning during the pandemic which is now a concern, namely the occurrence of learning loss in students. Learning loss as a decrease in learning competence in students. Learning loss occurs due to several factors including first, prolonged Distance Learning (PJJ), which after the implementation of a distance or online learning system by the government actually makes the teaching and learning process ineffective. The purpose of this study is to identify that blended learning is a mixture of various learning strategies and delivery methods that will optimize the learning experience for its users. The implementation of this strategy allows the use of online learning resources, especially those based on web/blogs, without leaving face-to-face activities. The research method used is quantitative method with this type of research is Quasi Experimental Design (quasi-experimental). Data collection techniques were carried out by observation, interviews and documentation studies. Data analysis techniques used the normality test, homogeneity test, hypothesis testing and normalized gain test to identify improvements in the results of the research conducted. The results of the data analysis show that there is an influence from the application of blended learning to the problem of learning loss in students. Then it shows that students' attitudes towards blended learning-based learning have an effect on problem patterns in the context of learning loss in students.